Hubungan Antara Beban Kerja dengan Stres Kerja Pada Pegawai Lapas Kelas IIA - Dewi Shinta Wulandari Lubis (Journal of Trends Economics and Accounting Research, 2023)
This study aims to look at the relationship between workload and work pressure on employees at Class II A Correctional Institution Ambon. The research approach used is a quantitative approach to the type of correlation research. The population in this study were employees in the security and guard team, totaling 85 people. To determine the number of samples in this study using a total sampling technique, namely the entire population is used as a research sample which also amounts to 85 people. Data collection was carried out using a scale of workload and work stress. Based on the results of data analysis using the correlational analysis method, it is known that there is a significant positive relationship between workload and work stress seen by the coefficient value (Rxy) = 0.758 with p = 0.000 <0.050, meaning that the hypothesis says there is a positive relationship between workload and work stress the higher the workload, the higher the work stress, and vice versa, the lower the workload, the lower the work stress received. In this study the workload on employees is high, based on the empirical average value obtained (71,43) is greater than the hypothetical average value (47). Furthermore, it is known that work stress on employees is high, this is based on the empirical average value obtained (114,71) which is greater than the hypothetical average value (95). Likewise with the value of the coefficient of determination (R2) which has a value of 0.694, this is equivalent to 69.4%, meaning that workload contributes 69.4% to work stress on employees. The effective contribution of workload affects work stress by 30,6%.